Functional and radioligand binding characterization of the α1L‐adrenoceptor subtype of the human vas deferens. (19th March 2015) - Davis, B. J.; Wiener, M.; Chapple, C. R.; Sellers, D. J.; Chess‐Williams, R.
Summary: Alpha1 ‐adrenoceptor antagonists can cause ejaculatory dysfunction as an adverse effect. Contractions of the human vas deferens are mediated via α1A ‐adrenoceptors, and this study investigated whether the low affinity state of this receptor (α1L ‐adrenoceptor) is involved in mediating contractions of this tissue. The potency of agonists and the affinity of receptor subtype selective antagonists were determined in functional experiments and in [ 3 H]tamsulosin binding experiments to identify the α1 ‐adrenoceptor subtype population present in the human vas deferens. The α1A ‐adrenoceptor selective agonist A61603 was a full agonist and was 250‐fold more potent than noradrenaline. Prazosin antagonized contractile responses to phenylephrine with a low affinity (pKd = 8.6). Only high concentrations of RS17053 antagonized responses to phenylephrine and yielded a relatively low affinity estimate of 7.0. BMY7378 (α1D ‐adrenoceptor selective) gave a low affinity estimate (pKd = 6.7), whilst tamsulosin (α1A ‐ and α1D ‐adrenoceptor selective) had a high affinity (pKd = 9.9). [ 3 H]Tamsulosin bound to human vas deferens membranes with a high affinity (pKd = 10.0). Prazosin, RS17053 and BMY7378 competed with [ 3 H]tamsulosin with low affinities for a single population of binding sites (pKd values of 8.5, 7.2 and 6.3, respectively). These functional and radioligand binding data indicate that the human vas deferens possesses a homogeneous population of α1 ‐adrenoceptors which have the pharmacological properties of the putative α1L ‐adrenoceptor, the same functional receptor previously identified in the human prostate.